Integrating Climate Risks in Bank Risk Management and Capital Requirements - Auzepy, Alix.; Bannier, Christina E.; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2025)
This open-access book provides readers with a comprehensive, practical and timely discussion of how to navigate the integration of climate-related considerations into bank risk management, including key methodologies, processes and implications. Climate risks pose new and complex challenges to traditional risk management. The authors examine the integration of climate risks into the risk management practices and capital requirements of large credit institutions, with a focus on entities supervised by the European Central Bank (ECB). Drawing on insights from expert interviews and disclosure reports, their analysis sheds light on both emerging approaches and key challenges. Focus areas, contextualized within the Basel framework, include minimum capital requirements for credit risk, internal capital adequacy assessments (covering risk identification, quantification, stress testing and capital allocation), risk appetite frameworks, and supervisory review processes. Contents Internal models for credit risk Scenario analysis and climate stress tests Capital adequacy assessments Risk appetite frameworks Supervisory review process The authors Alix Auzepy is a research assistant and doctoral candidate at the Chair of Banking and Finance at the Justus-Liebig-University Giessen, Germany. Christina E. Bannier is a Professor of Banking and Finance at the Justus-Liebig-University Giessen, Germany.
Introduction -- Theoretical Background -- Research sample and method -- Results -- Discussion and conclusion.
Keywords: Financial services industry; Financial Services